The Relationship of Gender Roles and Beliefs to Crying in an International Sample - Sharman, Leah S.; Dingle, Genevieve A.; Baker, Marc; Fischer, Agneta; Gračanin, Asmir; Kardum, Igor; Manley, Harry; Manokara, Kunalan; Pattara-angkoon, Sirirada; Vingerhoets, Ad J. J. M.; Vanman, Eric J. (Frontiers in Psychology, 2019)
This study aimed to (1) investigate the variation in self ascription to gender roles and attitudes toward gender roles across countries and its associations with crying behaviors, emotion change, and beliefs about crying, and (2) understand how the presence of others affects our evaluations of emotion following crying. This was a large international survey design study (N = 893) conducted in Australia, Croatia, the Netherlands, Thailand, and the United Kingdom. Analyses revealed that, across countries, gender, self-ascribed gender roles, and gender role attitudes were related to behavioral crying responses, but not related to emotion change following crying. How a person evaluates crying, instead, appeared to be highly related to one’s beliefs about the helpfulness of crying, irrespective of gender. Results regarding crying when others were present showed that people are more likely both to cry and to feel that they received help around a person that they know, compared to a stranger. Furthermore, closeness to persons present during crying did not affect whether help was provided. When a crier reported that they were helped, they also tended to report feeling better following crying than those who cried around others but did not receive help. Few cross-country differences emerged, suggesting that a person’s responses to crying are quite consistent among the countries investigated here, with regard to its relationship with a person’s gender role, crying beliefs, and reactions to the presence of others.